Penerapan Sertifikat CHSE Terhadap Kepuasan Pengunjung di Devoyage Bogor - Rima Pratiwi Batubara; Wulan Suci (Altasia Jurnal Pariwisata Indonesia, 2022)
Devoyage Bogor is a tourist spot made for Instagramable photo hunters by carrying out the concept of European-style garden tourism with miniatures typical of blue continent countries such as the Eiffel tower landmark, Dutch windmills and Venetian Gondolas, making it very suitable for visits by all ages. The uniqueness of Devoyage Bogor itself has European-style miniature buildings that are made as similar as possible to the original. The purpose of this study is to identify the application of the CHSE Certificate for the Devoyage Bogor tourist attraction and measure the effect of the application of CHSE on visitor satisfaction at Devoyage Bogor. The method used is quantitative with the population, namely tourists who have visited the Devoyage Bogor tourist attraction after the issuance of the CHSE certificate by the Ministry of Tourism and Creative Economy to Devoyage Bogor. Distributing questionnaires using google form online and offline with a sample size of 100 respondents. Data analysis using Inferential Analysis Techniques, Normality Test, Linearity Test and Simple Linear Regression. The results of the conclusion in the study that Devoyage Bogor has implemented the CHSE Certificate in accordance with the guidelines made by the Ministry of Tourism and Creative Economy such as the availability of sinks in several areas, the application of distance keeping so that there is no accumulation in one photo spot, and creating beautiful and comfortable environmental conditions to visit. And there is a positive influence between the CHSE Certificate variable on Visitor Satisfaction where this is evidenced by the results of the T test, namely 14.213 so that the T table is smaller than the T count of 1.984 and the coefficient of determination with a value of 67% so that it has a significant influence while the remaining 33% is influenced by variables not examined.